Dispersion of surface-treated metal oxide particles and method for producing same

JP7637536B2Active Publication Date: 2025-02-28JGC CATALYSTS & CHEMICALS LTD
-1 Cites 0 Cited by

Patent Information

Application Number
JP2021041743
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-15
Publication Date
2025-02-28
Estimated Expiration
2041-03-15
Patent Text Reader

Abstract

To provide surface-treated metal oxide particles having high dispersibility in a dispersion medium or resin in which an organosilicon compound is precisely supported on the surface of the metal oxide particles.SOLUTION: A dispersion of surface-treated metal oxide particles containing 3 to 60 pts.mass, as solid content, of an organosilicon compound having functional groups relative to 100 pts.mass of the metal oxide particles. The organosilicon compound in the liquid, excluding the particles from the dispersion, is 0.20 pt.mass or less as solid content relative to the metal oxide particles. The average primary particle size (D) of the particles by image analysis is 5 to 120 nm, and the ratio (L / D) of the average primary particle size (D) to the average particle size (L) measured by dynamic light scattering is 1.0 to 1.5. According to this dispersion, a coating solution capable of producing a film having excellent adhesion to the substrate and having high hardness and strength can be obtained.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a dispersion of metal oxide particles whose surface has been treated with an organosilicon compound having a functional group, and a method for producing the same. [Background technology]

[0002] Conventionally, it has been known to form a transparent coating with hard coating function on the surface of a substrate to improve the pencil hardness (hardness) and scratch resistance (strength) of substrate surfaces such as glass, plastic sheets, and plastic lenses, as well as display devices. Specifically, a transparent organic resin film or inorganic film is formed on the surface of glass, plastic, display device substrates, etc. In this case, it is known that incorporating particles such as silica into the coating improves adhesion to the substrate, strength, etc. In addition, it is known that incorporating high-refractive-index particles such as titanium oxide or zirconium oxide into the coating reduces the refractive index difference between the coating and the substrate, thereby suppressing interference fringes, and incorporating conductive particles such as antimony pentoxide, tin-doped indium oxide, or antimony-doped tin oxide into the coating imparts antistatic properties. When using such metal oxide particles, it is known to surface treat them with an organosilicon compound to improve their dispersibility in matrix components (see, for example, Patent Document 1).

[0003] Metal oxide particles surface-treated with an organosilicon compound have a layer where the OH groups on the particle surface are chemically bonded to the organosilicon compound, and a layer where the two are physically adsorbed. The presence of this chemically bonded layer has the effect of suppressing particle aggregation in the resin, and the presence of the physically adsorbed layer is known to improve compatibility with the resin (see, for example, Patent Documents 2 and 3). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] WO2011 / 059081 [Patent Document 2] Japanese Patent Application Laid-Open No. 2005-298740 [Patent Document 3] Japanese Patent Application Laid-Open No. 2015-189637 Summary of the Invention [Problem to be solved by the invention]

[0005] Coated substrates using metal oxide particles surface-treated with an organosilicon compound are required to have high hardness and strength. Incidentally, when an organosilicon compound is physically adsorbed onto metal oxide particles, improved compatibility of the particles with resins is expected, resulting in improved hardness and strength. However, coated substrates using such surface-treated metal oxide particles do not have sufficient improvements in hardness and strength. This is thought to be because the presence of at least one of the physically adsorbed organosilicon compound and unreacted organosilicon compound on the metal oxide particles inhibits chemical bonding between the metal oxide particles and the resin to form three-dimensional crosslinks, resulting in insufficient coating density. Therefore, metal oxide particles with more precise surface treatments are required. Furthermore, these particles are required to have high dispersibility in a dispersion medium or resin. Furthermore, coated substrates using these particles are required to suppress particle aggregation and have sufficient hardness and strength. [Means for solving the problem]

[0006] To solve these problems, the inventors discovered the following dispersion of surface-treated metal oxide particles. This dispersion contains surface-treated metal oxide particles containing 3 to 60 parts by mass of an organosilicon compound having a functional group, as solid content, per 100 parts by mass of metal oxide particles. The amount of the organosilicon compound remaining in the liquid after removing the surface-treated metal oxide particles from the dispersion is 0.20 parts by mass or less, as solid content, per metal oxide particle.

[0007] The average primary particle diameter (D) of the surface-treated metal oxide particles determined by image analysis is 5 to 120 nm, and the ratio (L / D) of this to the average particle diameter (L) determined by dynamic light scattering is 1.0 to 1.5.

[0008] The surface-treated metal oxide particles have high dispersibility. They also have many polymerization sites with matrix-forming components and a small amount of "unreacted and physically adsorbed organosilicon compounds" that inhibit polymerization with the matrix-forming components. A coating solution containing such particles can produce a coated substrate with high hardness and strength.

[0009] In order to obtain these surface-treated metal oxide particles, the following production method was discovered.

[0010] First, a dispersion containing metal oxide particles is prepared, and an organosilicon compound represented by the following formula (1) is added to the dispersion to surface-treat the metal oxide particles (first step). Next, the organosilicon compound is removed from the dispersion of the surface-treated metal oxide particles (second step).

[0011] R n -SiX 4-n ...Equation (1) (In the formula, R represents an unsubstituted or substituted hydrocarbon group having 1 to 10 carbon atoms, and may be the same or different. Examples of the substituent include an alkyl group, a vinyl group, an epoxy group, an alkoxy group, a (meth)acryloxy group, a mercapto group, a glycidoxy group, a halogen atom, an amino group, a phenyl group, and a phenylamino group. X represents an alkoxy group having 1 to 4 carbon atoms, a hydroxyl group, a halogen atom, or a hydrogen atom, and n represents an integer of 0 to 4.)

[0012] The properties of the surface-treated metal oxide particles in the dispersion obtained in the second step are similar to the properties of the dispersion of surface-treated metal oxide particles described above. [Effects of the Invention]

[0013] The dispersion of surface-treated metal oxide particles of the present invention provides a coating solution that is excellent in adhesion to a substrate and can produce a coating film that has high hardness and strength. DETAILED DESCRIPTION OF THE INVENTION

[0014] [Dispersion of surface-treated metal oxide particles] The dispersion (hereinafter, sometimes simply referred to as "dispersion") of surface-treated metal oxide particles (hereinafter, sometimes simply referred to as "particles") according to the present invention will be described below.

[0015] The particles in the dispersion contain 3 to 60 parts by mass of an organosilicon compound having a functional group as solid content per 100 parts by mass of metal oxide particles, and the amount of the organosilicon compound in the liquid excluding the particles from the dispersion is 0.20 parts by mass or less as solid content per 100 parts by mass of metal oxide particles.

[0016] The average primary particle diameter (D) of the particles determined by image analysis is 5 to 120 nm, and the ratio (L / D) of this to the average particle diameter (L) of the particles determined by dynamic light scattering is 1.0 to 1.5.

[0017] The particles contain functional groups derived from a surface treatment agent (organosilicon compound represented by formula (1)). The functional groups are preferably at least one selected from vinyl groups, epoxy groups, alkoxy groups, (meth)acryloxy groups, mercapto groups, glycidoxy groups, halogen groups, amino groups, phenyl groups, and phenylamino groups. Among these, vinyl groups, epoxy groups, alkoxy groups, (meth)acryloxy groups, amino groups, and mercapto groups are more preferred because they have high polymerization ability.

[0018] The solid content of the organosilicon compound relative to the metal oxide particles can be calculated by thermogravimetry. Heating to 500°C leaves the metal oxide particles and silicon content derived from the organosilicon compound. Therefore, only the surface-treated metal oxide particles are extracted by centrifugation and heated at 500°C. The mass loss before and after heating is measured, and the amount of silicon derived from the organosilicon compound is calculated from the difference with the amount of metal oxide particles. Next, this is used to calculate the solid content (R) derived from the organosilicon compound from the structure of the organosilicon compound used for surface treatment. n -SiO (4-n) / 2 ) amount, the solid content of the organosilicon compound can be calculated.

[0019] When the particles contain 3 to 60 parts by mass of an organosilicon compound as a solid content per 100 parts by mass of metal oxide particles, the particles can exist in a dispersion without agglomeration or sedimentation. Furthermore, the particles have good dispersibility in a coating solution and a film, and the use of such particles can produce a film with high hardness and strength.

[0020] If the amount of organosilicon compound is less than 3 parts by mass, sufficient dispersibility and stability may not be obtained, and when these particles are used in a coating, the resulting coating may not have sufficient hardness and strength. Conversely, if the amount exceeds 60 parts by mass, the dispersibility and stability will not be further improved, and the hardness and strength of the coating will not be improved either. The amount of this organosilicon compound is preferably 3 to 45 parts by mass, more preferably 3 to 30 parts by mass.

[0021] The amount of organosilicon compounds in the dispersion liquid after removing the particles can be calculated by GC-MS measurement. By centrifuging, the particles settle, while the unreacted organosilicon compounds that have not reacted with the metal oxide particles are extracted into the supernatant. By performing GC-MS measurement on this supernatant, the amount of organosilicon compounds in the dispersion liquid after removing the particles can be calculated.

[0022] When the amount of organosilicon compound in the dispersion excluding the particles is 0.20 parts by weight or less in terms of solids per 100 parts by weight of metal oxide particles, this indicates that the amount of unreacted organosilicon compound and physically adsorbed organosilicon compound is low. If the amount of such organosilicon compound exceeds 0.20 parts by weight, when these particles are used in a coating, the resulting coating may not have sufficient hardness and strength. This is because the presence of unreacted organosilicon compound or physically adsorbed organosilicon compound reduces the degree of polymerization of the matrix-forming components during coating formation, preventing the formation of a dense film. The amount of this organosilicon compound is preferably 0.10 parts by weight or less, more preferably 0.08 parts by weight or less, even more preferably 0.05 parts by weight or less, and particularly preferably substantially 0 parts by weight. Here, "substantially 0 parts by weight" means that the amount of organosilicon compound is below the detection limit of the measuring instrument.

[0023] Thus, one of the characteristics of the particles of the present invention is that they have the necessary amount of "organosilicon compounds having functional groups" that are chemically bonded to the OH groups on the surface of the metal oxide particles, and the content of "unreacted and physically adsorbed organosilicon compounds" is suppressed, i.e., they have undergone "precise surface treatment."

[0024] The average primary particle diameter (D) determined by particle image analysis is 5 to 120 nm. When the average primary particle diameter (D) is within this range, the particles can exist in the dispersion without agglomeration or sedimentation. Furthermore, the particles have good dispersibility in the coating solution and in the film, resulting in a film with high transparency, hardness, and strength.

[0025] Here, it is difficult to obtain particles with an average primary particle diameter (D) of less than 5 nm. Conversely, if it exceeds 120 nm, a transparent coating may not be obtained. This average (D) is preferably 5 to 100 nm, more preferably 7 to 80 nm, and even more preferably 7 to 50 nm.

[0026] The ratio (L / D) of the average particle size (L) of the particles measured by dynamic light scattering to the average primary particle size (D) is 1.0 to 1.5. The ratio (L / D) in this range indicates that the proportion of agglomerated particles is low and the particles are in a monodispersed state. Therefore, the particles have high dispersibility in the dispersion medium or matrix-forming components. Furthermore, when formed into a coated substrate, high hardness, strength, and transparency are obtained.

[0027] If the ratio (L / D) exceeds 1.5, the coating may not have sufficient hardness, strength, and transparency.

[0028] The ratio (L / D) is preferably 1.0 to 1.4, and more preferably 1.0 to 1.3.

[0029] The metal oxide particles preferably contain at least one element selected from the group consisting of Si, Al, Sn, Sb, Ti, Zr, Zn, W, Fe, In, and Ba. These oxides may be used alone, in the form of a mixture, or in the form of a composite oxide. However, the content of these elements in the metal oxide particles is preferably 90% by mass or more, more preferably 95% by mass or more, even more preferably 98% by mass or more, and particularly preferably 100% by mass.

[0030] Pulsed NMR is a measurement method that excites magnetization in a thermal equilibrium state in a static magnetic field by irradiating it with pulsed radio waves of several tens of megahertz, and observes the phenomenon in which the excited magnetization returns to its original thermal equilibrium state over time. Here, liquid molecules that are in contact with or adsorbed to particle surfaces respond differently to changes in the magnetic field than free liquid molecules that are not in contact with the particle surfaces.

[0031] In general, the movement of liquid molecules adsorbed to particle surfaces is restricted, while liquid molecules not adsorbed to particle surfaces can move freely. As a result, the relaxation time of liquid molecules adsorbed to particle surfaces is shorter than that of other liquid molecules. The relaxation time observed in a liquid containing dispersed particles is the average of two relaxation times reflecting the liquid volume concentration on the particle surfaces and the liquid volume concentration in the free state.

[0032] In a dispersion of metal oxide particles surface-treated with an organosilicon compound, in addition to the organosilicon compound chemically bonded to the metal oxide particles, there may be unreacted organosilicon compounds that are not chemically bonded to the metal oxide particles and organosilicon compounds that are only physically adsorbed. These organosilicon compounds have a much smaller molecular weight than the metal oxide particles, and therefore have a very large specific surface area. Furthermore, since the movement of liquid molecules adsorbed to these unreacted and physically adsorbed organosilicon compounds relative to the particles in the dispersion is restricted, when unreacted and physically adsorbed organosilicon compounds are present in the dispersion, the measured relaxation time will be shorter, i.e., the specific surface area calculated from the relaxation time will be a large value.

[0033] The specific surface area (A1) of particles in a dispersion determined by pulsed NMR measurement represents the specific surface area of ​​the particles in the portion wetted by the dispersion medium. Metal oxide particles surface-treated with an organosilicon compound have fewer OH groups on their surface due to the reaction between the organosilicon compound and the OH groups on the particle surface, resulting in a small specific surface area of ​​the particles in the portion wetted by the hydrophilic dispersion medium. In contrast, unreacted organosilicon compounds and metal oxide particles with only physically adsorbed organosilicon compounds retain residual OH groups, and therefore, when these are present in the dispersion, the specific surface area of ​​the portion wetted by the hydrophilic dispersion medium is large. Therefore, the specific surface area (A1) varies depending on the degree of surface treatment (chemical bonding) of the organosilicon compound on the metal oxide particles and the amount of unreacted organosilicon compounds and physically adsorbed organosilicon compounds in the dispersion. The specific surface area (A1) also varies depending on the type of dispersion medium used during measurement.

[0034] On the other hand, the specific surface area (A2) calculated from the average primary particle diameter (F) of metal oxide particles roughly corresponds to the specific surface area measured by the BET method. Therefore, the ratio (A1 / A2) of the specific surface area (A1) of "surface-treated metal oxide particles" to the specific surface area (A2) of "untreated metal oxide particles" is an indicator of the degree of hydrophobicity of the particle surface and the amount of unreacted and physically adsorbed organosilicon compounds in the dispersion. Here, the ratio (A1 / A2) of the specific surface area (A1) obtained from pulse NMR measurement of a methanol dispersion of surface-treated metal oxide particles to the specific surface area (A2) calculated from the average primary particle diameter (F) of the metal oxide particles is preferably 0.80 or less. A ratio (A1 / A2) in this range indicates that the particle surfaces are sufficiently hydrophobic and that the amount of unreacted and physically adsorbed organosilicon compounds in the dispersion is low. The use of such particles allows for good dispersibility in the coating solution and in the film, resulting in a film with high transparency, hardness, and strength.

[0035] If the ratio (A1 / A2) exceeds 0.80, the hydrophobicity of the particle surface may be insufficient, or a large amount of unreacted organosilicon compound or physically adsorbed organosilicon compound may remain in the dispersion. The lower limit of the ratio (A1 / A2) is not particularly set, but considering the particle size, it is, for example, 0.30. The ratio (A1 / A2) is more preferably 0.70 or less, and even more preferably 0.65 or less.

[0036] The specific surface area (A1) of the particles is obtained by the formula (3) using the volume concentration (Ψp) of the metal oxide particles calculated by the following formula (2).

[0037] Ψp=(Sc / Sd) / [(1-Sc) / Td] Formula (2) (where Sc is the solid concentration (mass%) of the metal oxide particles in the dispersion, and Sd is the density (g / cm 3 ), and Td is the density of the dispersion medium at 25°C (g / cm 3 ) indicates.

[0038] Here, the solids concentration refers to the concentration of the target substance (here, metal oxide particles) converted into solids in the dispersion (the same applies below). For example, Sd is 2.2 when the constituent component of the metal oxide particles is silica; 3.9 when it is alumina; 6.9 when it is tin oxide; 5.2 when it is antimony oxide; 3.9 when it is titania (anatase); 4.3 when it is titania (rutile); 6.0 when it is zirconia; 5.6 when it is zinc oxide; 7.2 when it is tungsten oxide; 5.2 when it is iron (III) oxide; 7.2 when it is indium oxide; and 5.7 when it is barium oxide. When the metal oxide particles are composite oxide particles, particles containing mixed oxides, or a mixture of oxide particles, Sd can be calculated according to the proportion of the oxides. For example, Td is 0.79 when the dispersion medium is methanol. If another type of dispersion medium or a mixture of dispersion mediums is used, the corresponding density should be used.

[0039] A1={[(Ra / Rb)-1]×Rb} / (Ka×Ψp)...Equation (3) (where A1 is the specific surface area of ​​the particle (m 2 / g), Ra is the inverse of the pulse NMR relaxation time in the measurement of the dispersion liquid, Rb is the inverse of the pulse NMR relaxation time in the measurement of the dispersion medium, and Ka is a coefficient depending on the dispersion medium and metal oxide particles used.

[0040] The coefficient Ka is calculated assuming that the specific surface area (A2) obtained from the average primary particle diameter (F) of the metal oxide particles is the same as the specific surface area (A3) obtained by pulse NMR measurement of a dispersion of the metal oxide particles.

[0041] The specific surface area (A2) of the metal oxide particles can be calculated using the average primary particle diameter (F) of the metal oxide particles according to the following formula (4).

[0042] A2=6000 / Sd / F...Formula (4) (where Sd is the density of the metal oxide particles (g / cm 3 ) indicates.

[0043] The specific surface area (A3) of the metal oxide particles is obtained from equation (5) using the volume concentration (Ψp) of the metal oxide particles obtained from equation (2).

[0044] A3={[(Rc / Rd)-1]×Rd} / (Ka×Ψp)...Equation (5) (where A3 is the specific surface area of ​​the metal oxide particles (m 2 / g), Rc is the reciprocal of the pulse NMR relaxation time in the measurement of the metal oxide particle dispersion, Rd is the reciprocal of the pulse NMR relaxation time in the measurement of the dispersion medium, and Ka is a coefficient depending on the dispersion medium and metal oxide particles used.

[0045] Here, the coefficient Ka is set so that the specific surface area (A2) and the specific surface area (A3) have the same value, so from equations (4) and (5), Ka={[(Rc / Rd)-1]×Rd} / (Ψp×A2)...Equation (6) It can be calculated as:

[0046] The dispersion medium and concentration of the dispersion liquid are not particularly limited as long as the particles are stably dispersed in the liquid without aggregation or precipitation.

[0047] Examples of the dispersion medium include alcohols, esters, glycols, ethers, ketones, etc. These may be used alone or in combination of two or more.

[0048] The concentration of the dispersion is preferably 0.1 to 50% by mass in terms of solid content as metal oxide. If the concentration is less than 0.1% by mass, the processing time required for producing the coating liquid may be long. Conversely, if the concentration exceeds 50% by mass, the stability of the dispersion may decrease. The concentration of the dispersion is more preferably 5 to 45% by mass, and even more preferably 10 to 40% by mass.

[0049] The content of each of the alkali metal and alkaline earth metal elements, which are impurities of the particles, expressed as oxides of the elements is preferably 500 ppm or less relative to the particles. This reduces particle coalescence, resulting in high stability of the dispersion and coating solution. Furthermore, the particles are uniformly dispersed in the coating solution and the film, resulting in a film with high hardness and strength.

[0050] Here, if the content of each element is more than 500 ppm, the rate of adhesion between particles increases, which may result in insufficient stability of the dispersion or coating solution, or insufficient hardness and strength of the coating. The content is more preferably 100 ppm or less. The alkali metals represent Li, Na, K, Rb, Cs, and Fr, and the alkaline earth metals represent Be, Mg, Ca, Sr, Ba, and Ra.

[0051] The shape of the particles is not particularly limited. Examples include spherical, ellipsoidal (rugby ball), cocoon, confetti, chain, and dice shapes. Among these, spherical particles are preferred because they have high dispersibility and can be uniformly dispersed in the coating.

[0052] [Method for producing a dispersion of surface-treated metal oxide particles] The method for producing a dispersion of surface-treated metal oxide particles according to the present invention comprises, in order, a first step of surface-treating metal oxide particles with an organosilicon compound represented by formula (1) and a second step of removing the organosilicon compound from the dispersion of surface-treated metal oxide particles obtained in the first step, thereby obtaining a dispersion of surface-treated metal oxide particles with high dispersibility.

[0053] The surface-treated metal oxide particles produced in this manner are inhibited from agglomerating, and when used in a coating, have sufficient hardness and strength. Each step will be described below.

[0054] [First step] The metal oxide particles prepared as a starting material in this step are preferably oxides containing at least one element selected from the group consisting of Si, Al, Sn, Sb, Ti, Zr, Zn, W, Fe, In, and Ba. These oxides may be used alone, in mixtures, or as composite oxides. However, the content of these oxides in the particles is preferably 90% by mass or more, more preferably 95% by mass or more, even more preferably 98% by mass or more, and particularly preferably 100% by mass.

[0055] The surface treatment begins with preparing a dispersion of metal oxide particles. Water or alcohols such as methanol or ethanol are preferably used as the dispersion medium. A predetermined amount of an organosilicon compound represented by formula (1) is added to the dispersion, and the organosilicon compound is hydrolyzed. Water can be added as needed for this hydrolysis. The ratio (Mw / Mo) of the number of moles of water (Mw) to the number of moles of the organosilicon compound (Mo) added is preferably 1 or greater. If the ratio (Mw / Mo) is less than 1, hydrolysis may be insufficient, resulting in insufficient hardness, strength, transparency, haze, and other properties of the coating. While there is no particular upper limit for the ratio (Mw / Mo), a ratio of more than 200 may result in the hydrolysis reaction becoming too intense, resulting in polymerization of the organosilicon compounds, potentially hindering efficient treatment of the metal oxide surface with the organosilicon compound. Therefore, the upper limit is preferably 200. The ratio (Mw / Mo) is more preferably 1 to 100.

[0056] In this hydrolysis, an acid or alkali may be used as a catalyst for hydrolysis, if necessary. Among these, ammonia is preferred. When ammonia is used, it is easy to remove even if it remains in the dispersion, and the stability of the dispersion is easily maintained. The number of moles of ammonia to be added (M N ) and the mole number (Mo) of the organosilicon compound (M N / Mo) is preferably in the range of 0.005 to 5. Here, the ratio (M N If the ratio (M / Mo) is less than 0.005, hydrolysis may be insufficient, and the hardness, strength, transparency, haze, etc. of the coating may become insufficient. N If the ratio (M / Mo) exceeds 5, the hydrolysis reaction becomes intense, and the organosilicon compounds polymerize with each other, which may prevent efficient treatment of the metal oxide surface with the organosilicon compound.

[0057] The surface treatment is preferably carried out in a homogeneous system, and in order to promote chemical bonding between the metal oxide particles and the organosilicon compound, it is preferable to heat the dispersion medium at a temperature below the boiling point (for example, room temperature to 120°C) for 0.5 to 48 hours.

[0058] The metal oxide particles whose surfaces are chemically bonded to the organosilicon compound by this surface treatment exhibit high adhesion to the substrate and high hardness and strength when used in a coated substrate.

[0059] Examples of organosilicon compounds include those shown in Table 1. These organosilicon compounds may be present in the particles alone or in combination. In the surface treatment, these organosilicon compounds may be used alone or in combination, or may be used in stages with the same type, a mixture of multiple types, or multiple types separately.

[0060] [Table 1]

[0061] [Second process] The organosilicon compounds surface-treated in the first step contain unreacted organosilicon compounds and organosilicon compounds that are only physically adsorbed, in addition to those chemically bonded to the metal oxide particles. The second step aims to remove "unreacted and physically adsorbed organosilicon compounds" from the metal oxide particles. Methods for removing these organosilicon compounds from the surface-treated metal oxide particles include, for example, ultrafiltration membrane methods, centrifugation methods, and distillation methods. Among these, the ultrafiltration membrane method is preferred due to its high removal efficiency. Ultrasonic treatment may also be combined to separate only physically adsorbed organosilicon compounds from the metal oxide particles.

[0062] To efficiently remove the organosilicon compounds, the metal oxide concentration of the dispersion of the surface-treated metal oxide particles in the first step is preferably 10 to 60% by mass in terms of solids. If the concentration is less than 10% by mass, the amount of cleaning solution used in the second step will be too large relative to the surface-treated metal oxide particles obtained, resulting in poor productivity. Conversely, if the concentration exceeds 60% by mass, thickening or gelation may occur during the second step. The amount of cleaning solution used for removing the organosilicon compounds is preferably at least three times the amount of the dispersion of the surface-treated metal oxide particles in the first step, depending on the amount of surface treatment in the first step and the concentration of the dispersion. If the amount of cleaning solution is less than three times, the removal of the organosilicon compounds may be insufficient. While there is no upper limit to the amount of cleaning solution, using more than 10 times the amount does not significantly improve the removal of the organosilicon compounds, so for example, 10 times the amount is preferred. It is preferable to use the same type of cleaning solution as the dispersion medium used in the first step.

[0063] Here, since the removal in the second step removes at least a portion of the organosilicon compound added in the first step, the amount of organosilicon compound added in the first step does not remain on the particles. Therefore, it is necessary to achieve both that the final amount of organosilicon compound having functional groups contained in the particles is 3 to 60 parts by weight (solids) per 100 parts by weight of metal oxide particles, and that the amount of organosilicon compound in the liquid after removing the particles from the dispersion is 0.20 parts by weight or less (solids) per 100 parts by weight of metal oxide particles. This allows for a "precise surface treatment" in which the necessary amount of "organosilicon compound having functional groups" chemically bonded to the OH groups on the metal oxide particle surface is present, while the content of "unreacted and physically adsorbed organosilicon compound" that may cause performance degradation is suppressed.

[0064] The particles obtained have an average primary particle diameter (D) of 5 to 120 nm as determined by image analysis, and the ratio (L / D) of this to the average particle diameter (L) of the particles as determined by dynamic light scattering is 1.0 to 1.5.

[0065] The preferred ranges of these physical properties are the same as those of the surface-treated metal oxide particles described above.

[0066] However, although this may be due to differences in the amount of surface treatment, it may be difficult to satisfy the two ranges mentioned above, "the amount of organosilicon compound having functional groups contained in the particles" and "the amount of organosilicon compound in the liquid excluding the particles," in a single operation from the first step to the second step. This depends on the reaction efficiency between the OH groups on the surface of the metal oxide particles and the organosilicon compound. In order to promote chemical bonding with the OH groups on the surface of the metal oxide particles and efficiently obtain the desired particles, it is preferable to perform the first step to the second step, and then repeat the first step to the second step multiple times. Furthermore, "precise surface treatment" can be achieved more efficiently by repeating the process with a surface treatment amount per time that is less than the final target amount.

[0067] [Coating liquid for film formation] The particles of the present invention can be used in a coating solution for forming a film. This coating solution contains particles, a matrix-forming component, and an organic dispersion medium. In addition, the coating solution may contain additives such as a polymerization initiator, a leveling agent, and a surfactant.

[0068] The concentration of particles in the coating liquid is preferably 20 to 70 mass % in terms of solid content relative to the total amount of solid content such as the particles and matrix-forming components contained therein.

[0069] If the particle concentration is less than 20% by mass, the hardness of the coating may be insufficient. Conversely, if it is more than 70% by mass, cracks may occur in the coating, adhesion to the substrate may be insufficient, and hardness, strength, transparency, haze, etc. may be deteriorated. The particle concentration is more preferably 30 to 65% by mass, and even more preferably 40 to 60% by mass.

[0070] The matrix-forming component is preferably an organic resin-based matrix-forming component, such as a matrix-forming component of an ultraviolet-curable resin, a thermosetting resin, or a thermoplastic resin.

[0071] Examples of ultraviolet curable resins include (meth)acrylic resins, γ-glycyloxy resins, urethane resins, and vinyl resins.

[0072] Examples of thermosetting resins include urethane resins, melamine resins, silicon resins, butyral resins, reactive silicone resins, phenolic resins, epoxy resins, unsaturated polyester resins, and thermosetting acrylic resins.

[0073] Thermoplastic resins include polyester resin, polycarbonate resin, polyamide resin, polyphenylene oxide resin, thermoplastic acrylic resin, vinyl chloride resin, fluororesin, vinyl acetate resin, silicone rubber, and the like.

[0074] These resins may be copolymers or modified products of two or more kinds, or may be used in combination. Furthermore, these resins may be emulsion resins, water-soluble resins, or hydrophilic resins.

[0075] The components forming these resins are preferably monomers or oligomers in view of particle dispersibility and ease of coating.

[0076] The concentration of the matrix-forming component in the coating liquid is preferably 30 to 80% by mass in terms of solid content relative to the total amount of solid content such as the particles and matrix-forming component contained therein.

[0077] If the concentration of the matrix-forming component is less than 30% by mass, it is difficult to form a coating. Even if a coating is obtained, cracks may occur in the coating, adhesion to the substrate may be insufficient, and hardness, strength, transparency, haze, etc. may be deteriorated. Conversely, if it is more than 80% by mass, the amount of particles may be small, and the hardness of the coating may be insufficient. The concentration of this matrix-forming component is more preferably 35 to 70% by mass, and even more preferably 40 to 60% by mass.

[0078] As the organic dispersion medium, one that can uniformly disperse particles and dissolve or disperse additives such as matrix-forming components and polymerization initiators is used. Among these, hydrophilic dispersion media and polar dispersion media are preferred. As shown in Table 2, examples of hydrophilic dispersion media include alcohols, esters, glycols, and ethers. Examples of polar dispersion media include esters and ketones. These may be used alone or in combination of two or more.

[0079] [Table 2]

[0080] Any additives that can be conventionally used for film formation can be used, such as a polymerization initiator and a leveling agent, which can be used to promote polymerization of the matrix-forming components and improve film-forming properties.

[0081] Examples of the polymerization initiator include those shown in Table 3.

[0082] Examples of the leveling agent include acrylic leveling agents, silicone leveling agents, acrylic silicone leveling agents, etc. Among these leveling agents, those having a fluorine group are preferably used from the viewpoint of improving strength.

[0083] Regarding the concentration of these additives in the coating solution, those contained as solids when the coating is formed are counted as matrix-forming components for convenience, and are counted as the matrix after the coating is formed.

[0084] [Table 3]

[0085] The solid content concentration of the coating liquid (the ratio of the total solid content of the particles and the matrix-forming components to the coating liquid) is preferably 1 to 60% by mass.

[0086] Here, if the solids concentration of the coating solution is less than 1% by mass, the coating will have low concentration stability, making coating difficult and possibly failing to produce a uniform coating. Furthermore, haze or poor appearance may result, potentially reducing productivity, manufacturing reliability, and the like. Conversely, if the solids concentration is higher than 60% by mass, the stability of the coating solution may be reduced. Furthermore, the viscosity of the coating solution may increase, potentially reducing coatability. Furthermore, the haze of the coating may increase, potentially resulting in insufficient strength. The solids concentration of the coating solution is more preferably 5 to 50% by mass.

[0087] [Substrate with coating] The coating liquid is used to form a coating on a substrate, and the resulting coating is preferably transparent from the viewpoint of visibility.

[0088] Specifically, the coating liquid is applied to a substrate, followed by drying and ultraviolet irradiation to form a coating on the substrate. The method for applying the coating liquid is not particularly limited as long as it can form a coating on the substrate. Well-known methods such as spraying, spinning, roll coating, bar coating, slit coater printing, gravure printing, and microgravure printing can be used. Drying involves heating to, for example, about 50 to 150°C to evaporate and remove the dispersion medium. Then, ultraviolet irradiation is performed to promote polymerization of the resin component, thereby increasing the hardness of the coating. The coating is mainly formed from a matrix (resin) component and particles.

[0089] In the coating, the ratio of the solid content of the particles and matrix-forming components in the coating solution is the same as the ratio of the particle components and matrix in the coating. As mentioned above, the additives remaining as solids in the coating solution are counted as the matrix.

[0090] The thickness of the coating can be appropriately selected depending on the application, for example, in the case of a hard coat film, it is preferably 0.5 to 20 μm.

[0091] Here, if the film thickness is less than 0.5 μm, the hardness and strength of the coating may be insufficient. Conversely, if the film thickness is greater than 20 μm, the film shrinkage may be large, causing significant curling or insufficient adhesion to the substrate. Furthermore, if the shrinkage is too large, cracks may occur. This film thickness is more preferably 1 to 15 μm, and even more preferably 4 to 12 μm.

[0092] The light transmittance of the coated substrate is preferably 85.0% or more.

[0093] Here, if the light transmittance is less than 85.0%, the clarity of the image may be insufficient in a display device, etc. The light transmittance is more preferably 90.0% or more.

[0094] The haze of the coated substrate is preferably 1.0% or less, and more preferably 0.5% or less.

[0095] The strength of the coating (scratch resistance) was measured using #0000 steel wool with a load of 1 kg / cm 2 The abrasion resistance is evaluated by rubbing the film against a surface of the film at a temperature of 100°C. It is preferable that no streaky scratches are observed on the film surface after at least 40 rubbings. More preferably, no scratches are observed after 60 rubbings, and even more preferably, no scratches are observed after 100 rubbings.

[0096] The pencil hardness of the coating is preferably 3H or more.

[0097] If the pencil hardness is less than 3H, the hardness is insufficient for a hard coat film.The pencil hardness is more preferably 4H or more, and even more preferably 5H or more.

[0098] Known substrates can be used. For example, transparent resin substrates such as polycarbonate, acrylic resin, polyethylene terephthalate, triacetyl cellulose (TAC), polymethyl methacrylate resin, and cycloolefin polymer are preferred. These substrates have excellent adhesion to the coating film formed by the above-mentioned coating liquid, and a coated substrate with excellent hardness, strength, etc. can be obtained. For this reason, they are suitable for use with thin substrates. There are no particular restrictions on the thickness of the substrate, but it is preferably 20 to 100 μm, more preferably 30 to 80 μm.

[0099] The adhesion between the coating and the substrate is preferably achieved by scratching the surface of the coated substrate with a knife in a grid pattern, adhering cellophane tape to the scratched surface, and then peeling off the cellophane tape. The more grid patterns that remain, the more likely the coating will not peel off and the higher the adhesion to the substrate.

[0100] Furthermore, a coated substrate having another coating formed on the substrate can also be used. Examples of the other coating include conventionally known anti-reflection coatings, primer coatings, high refractive index coatings, conductive coatings, etc.

[0101] Examples of the present invention will be described below.

[0102] [Example 1] <Preparation of Dispersion of Metal Oxide Particles> 2000 g of an aqueous dispersion of silica particles (JGC Catalysts and Chemicals Co., Ltd., Cataloid SI-30, solids concentration 30% by mass) was subjected to ion exchange for 3 hours using 300 g of a cation exchange resin (Mitsubishi Chemical Corporation, Diaion SK-1BH). 200 g of an anion exchange resin (Mitsubishi Chemical Corporation, Diaion SA-20A) was then subjected to ion exchange for 3 hours using 100 g of a cation exchange resin at 80°C to prepare an aqueous dispersion of silica particles. The dispersion medium was then replaced with methanol by ultrafiltration, and the mixture was concentrated to prepare a methanol dispersion of silica particles with a solids concentration of 30% by mass.

[0103] <Surface treatment of metal oxide particles with organosilicon compounds (first step)> To 2000 g of this methanol dispersion of silica particles, 4.4 g of ammonia water with a concentration of 28% by mass and 39.8 g of pure water were added, and the mixture was stirred at room temperature for 0.5 hours.

[0104] Next, 90 g of γ-methacryloxypropyltrimethoxysilane (KBM-503 manufactured by Shin-Etsu Chemical Co., Ltd.) was added as an organic silicon compound (R n -SiX 4-n The mixture was stirred at 50° C. for 19 hours to obtain a dispersion of surface-treated silica particles.

[0105] <Removal of organosilicon compounds (second step)> This dispersion of surface-treated silica particles was cooled to room temperature, and 10 kg of methanol (equivalent to five times the amount of the methanol dispersion of silica particles) was used to remove the "unreacted and physically adsorbed organosilicon compounds" by ultrafiltration membrane method, producing a methanol dispersion of surface-treated silica particles of the present invention with a solid content concentration of 30 mass% as metal oxide particles.

[0106] The dispersion of the surface-treated metal oxide particles was measured by the following method.

[0107] The characteristics of each particle production process, and the properties of the particles and dispersion liquid are shown in Table 4 (the same applies to the following Examples and Comparative Examples).

[0108] (1) Organosilicon compounds with functional groups The presence or absence of functional groups contained in the particles and the types thereof were determined by the following method.

[0109] First, the dispersion liquid was dried in an evaporator and then dried at 150° C. The powder was analyzed by a diffuse reflectance method using a Fourier transform infrared spectrometer (FT-IR) (FT / IR-6100 manufactured by JASCO Corporation) in the wavenumber range of 700 cm -1 ~4000cm -1 , detector: TGS, resolution: 4.0 cm -1Measurements were performed with 50 accumulations, peaks were detected, and functional groups were identified by referring to the organic compound spectrum database SDBS (https: / / sdbs.db.aist.go.jp (National Institute of Advanced Industrial Science and Technology, 2021.01)).

[0110] (2) Solid content of organosilicon compound having functional groups The dispersion was centrifuged for 30 minutes using a small ultracentrifuge (Hitachi Koki Co., Ltd., CS150GXL) at a temperature of 10°C and a rotation speed of 1,370,000 rpm (1,000,000 G). The precipitate from the treatment solution was collected and dried under vacuum. The mass loss before and after heating to 500°C was measured using a thermogravimetric differential thermal analyzer (Hitachi High-Tech Science Co., Ltd., TG / DTA EXSTAR6000 MSD). The amount of silicon derived from the organosilicon compound was calculated from the difference with the amount of metal oxide particles. Next, the solid content (R) derived from the organosilicon compound was determined from the structure of the organosilicon compound used in the surface treatment. n -SiO (4-n) / 2 The solid content of the organosilicon compound having a functional group was calculated by converting the amount of the solid content into the amount of the organosilicon compound having a functional group.

[0111] (3) Amount of organosilicon compound in the liquid after removing particles from the dispersion The dispersion was centrifuged in a small ultracentrifuge (Hitachi Koki Co., Ltd., CS150GXL) in the same manner as described above. The supernatant was collected and the amount of organosilicon compounds in the liquid, excluding the particles, was measured using a thermal extraction gas chromatograph (Agilent Technologies, Inc., Agilent 5977BGC / MSD).

[0112] (4) Average primary particle size of particles (D) and average primary particle size of metal oxide particles (F) The particle dispersion was diluted to 0.01% by mass and then dried on a collodion film in a copper cell for an electron microscope. It was then photographed at a predetermined magnification using a field-emission scanning electron microscope (S-5500, manufactured by Hitachi High-Technologies Corporation). The particle area of ​​300 randomly selected particles in the resulting photographic projection (SEM image) was calculated by image processing, and the equivalent circle diameter was calculated from the area. The average of the equivalent circle diameters was taken as the average primary particle diameter (D).

[0113] Similarly, the dispersion of silica particles was also subjected to image analysis to determine the average primary particle size (F) of the silica particles.

[0114] (5) Average particle size (L) measured by dynamic light scattering The dispersion was adjusted to an appropriate concentration using ethanol, and the particle size was measured using a dynamic light scattering particle size analyzer (FPAR-1000, manufactured by Otsuka Electronics Co., Ltd.) to obtain the average particle size (L). Here, the appropriate concentration means a concentration at which the scattered light intensity is 15,000 to 30,000 CPS. The measurement was performed under the conditions of a solvent refractive index of 1.3614 and a temperature of 20°C.

[0115] (6) Content of metal elements, alkali metals, and alkaline earth metals The contents of metal elements (Si, Al, Sn, Sb, Ti, Zr, Zn, W, Fe, In, Ba), alkali metals, and alkaline earth metals in the particles and metal oxide particles were measured by dissolving the particles in hydrofluoric acid, heating to remove the hydrofluoric acid, adding pure water as needed, and then measuring the resulting solution using an ICP inductively coupled plasma optical emission spectrometer mass spectrometer (ICP-8500, manufactured by Shimadzu Corporation).

[0116] (7) Specific surface area (A1) by pulsed NMR Using pulse NMR (Acorn Area manufactured by Xigo nanotools), the relaxation times of the dispersion liquid and the dispersion medium were measured, and the specific surface area (A1) was calculated using the above-mentioned formula (2). The measurement conditions were a magnetic field of 0.3 T, a measurement frequency of 13 MHz, and a measurement nucleus of 1The H NMR measurement was performed by CPMG pulse sequence method with a sample volume of 1 ml, a Ka value of 0.000039, and a temperature of 25° C. Here, the Ka value was calculated using the above-mentioned formulas (4) to (6) by performing pulse NMR measurement on a methanol dispersion of metal oxide particles (here, silica particles) with a solid content of 30 mass % at 25° C. and the methanol dispersion medium.

[0117] (8) Specific surface area (A2) The specific surface area (A2) was calculated using the average primary particle diameter (F) of the metal oxide particles according to the following formula (4).

[0118] A2=6000 / Sd / F...Formula (4) (where Sd is the density of the metal oxide particles (g / cm 3 ) indicates.

[0119] <Production of Coating Solution for Film Formation> The methanol dispersion of the produced surface-treated silica particles was replaced with methyl isobutyl ketone (MIBK) using centrifugation and ultrasonic dispersion methods, and an MIBK dispersion of surface-treated silica particles with a solid content of 40 mass% was prepared.

[0120] 6.00 g of the MIBK dispersion of these particles, 1.60 g of a multifunctional acrylate resin (Light Acrylate DPE-6A, manufactured by Kyoeisha Chemical Co., Ltd.), 0.10 g of a photopolymerization initiator (Omnirad 184, manufactured by IGM Resins BV), 0.10 g of an acrylic silicone leveling agent (Disparlon NSH-8430HF, manufactured by Kusumoto Chemical Co., Ltd., solids concentration 10% by mass), 1.20 g of MIBK, and 1.00 g of acetone were thoroughly mixed to produce a coating solution for forming a coating with a solids concentration of 40% by mass.

[0121] <Production of coated substrate> This coating solution was applied to a TAC film (FT-PB40UL-M, manufactured by Fujifilm Corporation, thickness 40 μm) using a bar coater (#16), dried at 80°C for 120 seconds, and then heated at 300 mJ / cm under a N2 atmosphere. 2The coating was cured by irradiation with ultraviolet light of 1000 kJ / min to produce a coated substrate.

[0122] The coated substrate was measured for the following items, and the results are shown in Table 5 (the same applies to the following Examples and Comparative Examples).

[0123] (9) Film Thickness The film thickness was determined as the average value of measurements taken at any five points on the film using a digital gauge (gauge stand ST-0230 and digital gauge counter DG-5100, manufactured by Ono Sokki Co., Ltd.).

[0124] (10) Haze, total light transmittance The haze and total light transmittance of the coated substrate were measured using a haze meter (NDH-5000 manufactured by Nippon Denshoku Industries Co., Ltd.).

[0125] (11) Measurement of scratch resistance Use #0000 steel wool and apply a load of 1kg / cm 2 The coating surface was visually inspected after each sliding cycle and the strength was evaluated according to the following criteria: Evaluation criteria: 60 times or more: ◎ 40 to less than 60 times: ○ 20 to less than 40 times: △ 20 times or less :×

[0126] (12)Pencil hardness The pencil hardness was measured using a pencil hardness tester in accordance with JIS K 5400. That is, a pencil was set at a 45-degree angle to the coating surface, and a predetermined load was applied and pulled at a constant speed to observe whether scratches were present. The hardness was evaluated according to the following classification. Evaluation criteria: 4H or more:◎ 3H:○ 2H:△ H or less: ×

[0127] (13) Overall evaluation of strength and hardness The scratch resistance and pencil hardness were evaluated and scored as follows: ◎:4 points ○:3 points △:2 points ×: 1 point

[0128] Using these scores, a total score was calculated using the following formula, and an overall judgment was made by classifying into four levels.

[0129] Total score calculation formula: (pencil hardness score) x (scratch resistance score)

[0130] The overall evaluation was as follows: "◎" or "○" was considered a pass. 12 or more and 16 or less:◎ 9 or more but less than 12 times: ○ 6 or more and less than 9: △ Less than 6: ×

[0131] (14) Adhesion The surface of the coated substrate was scratched with a knife in 11 parallel lines spaced 1 mm apart to create 100 squares, to which cellophane tape was adhered. The cellophane tape was then peeled off and the number of squares where the coating remained was counted. The results were classified as follows to evaluate adhesion. Evaluation criteria: Number of remaining squares: 100 Number of remaining squares: 99 or less: ×

[0132] [Example 2] In Example 1, after the second step, the first step and the second step were again carried out in this order to produce a methanol dispersion of surface-treated silica particles (the first step and the second step were repeated twice).

[0133] Next, a coating solution and a coated substrate were produced in the same manner as in Example 1, except that this dispersion was used, and the properties were evaluated.

[0134] [Example 3] 30 g of γ-methacryloxypropyltrimethoxysilane (R per 100 parts by mass of silica particles) n -SiX 4-nA methanol dispersion of surface-treated silica particles was prepared in the same manner as in Example 2, except that 5 parts by mass of the surface-treated silica particles was used.

[0135] Next, a coating solution and a coated substrate were produced in the same manner as in Example 1, except that this dispersion was used, and the properties were evaluated.

[0136] [Example 4] 300 g of γ-methacryloxypropyltrimethoxysilane (R n -SiX 4-n A methanol dispersion of surface-treated silica particles was produced in the same manner as in Example 1, except that 50 parts by mass of the solvent (as a solvent) was used and the first step and the second step were repeated 10 times in order.

[0137] Next, a coating solution and a coated substrate were produced in the same manner as in Example 1, except that this dispersion was used, and the properties were evaluated.

[0138] [Example 5] A methanol dispersion of surface-treated silica particles was produced in the same manner as in Example 2, except that 6 kg of methanol was used in the second step.

[0139] Next, a coating solution and a coated substrate were produced in the same manner as in Example 1, except that this dispersion was used, and the properties were evaluated.

[0140] [Example 6] A methanol dispersion of surface-treated silica particles was produced in the same manner as in Example 2, except that 4.8 kg of methanol was used in the second step.

[0141] Next, a coating solution and a coated substrate were produced in the same manner as in Example 1, except that this dispersion was used, and the properties were evaluated.

[0142] [Example 7] A methanol dispersion of surface-treated silica particles was produced in the same manner as in Example 2, except that 1,500 g of an aqueous dispersion of silica particles (Cataloid SI-80P manufactured by JGC Catalysts and Chemicals Co., Ltd., solid content concentration 40% by mass) was diluted with 500 g of water.

[0143] Next, a coating solution and a coated substrate were produced in the same manner as in Example 1, except that this dispersion was used, and the properties were evaluated.

[0144] [Example 8] The dispersion medium of 3750 g of an aqueous dispersion of silica-alumina particles (JGC Catalysts and Chemicals Co., Ltd., Cataloid SN-350, solid content concentration 16% by mass) was replaced with methanol by ultrafiltration, and then the mixture was concentrated to prepare a methanol dispersion of silica-alumina particles with a solid content concentration of 30% by mass. A methanol dispersion of surface-treated silica-alumina particles was produced in the same manner as in Example 2, except that this dispersion was used.

[0145] Next, a coating solution and a coated substrate were produced in the same manner as in Example 1, except that this dispersion was used, and the properties were evaluated.

[0146] [Example 9] A methanol dispersion of surface-treated silica particles was produced in the same manner as in Example 2, except that 3,000 g of an aqueous dispersion of silica particles (Cataloid SI-550 manufactured by JGC Catalysts and Chemicals Co., Ltd., solid content concentration 20% by mass) was used.

[0147] Next, a coating solution and a coated substrate were produced in the same manner as in Example 1, except that this dispersion was used, and the properties were evaluated.

[0148] [Example 10] A methanol dispersion of surface-treated silica particles was produced in the same manner as in Example 2, except that 3,333 g of an aqueous dispersion of silica particles (Spherica Slurry SS-120 manufactured by JGC Catalysts and Chemicals Co., Ltd., solid content concentration 18% by mass) was used.

[0149] Next, a coating solution and a coated substrate were produced in the same manner as in Example 1, except that this dispersion was used, and the properties were evaluated.

[0150] [Example 11] 1500 g of an aqueous dispersion of silica particles (JGC Catalysts and Chemicals Co., Ltd., Cataloid SI-80P) diluted with 500 g of water was mixed with 18 g of γ-methacryloxypropyltrimethoxysilane (R 18 g per 100 parts by mass of silica particles). n -SiX 4-n A methanol dispersion of surface-treated silica particles was prepared in the same manner as in Example 2, except that 3 parts by mass of the hydroxybenzoate was used.

[0151] Next, a coating solution and a coated substrate were produced in the same manner as in Example 1, except that this dispersion was used, and the properties were evaluated.

[0152] [Example 12] A dispersion medium of 3000 g of an aqueous dispersion of silica alumina particles (JGC Catalysts and Chemicals Co., Ltd., Cataloid SN, solid content concentration 20% by mass) was replaced with methanol by ultrafiltration, and then the mixture was concentrated to prepare a methanol dispersion of silica alumina particles with a solid content concentration of 30% by mass. A methanol dispersion of surface-treated silica particles was produced in the same manner as in Example 2, except that this dispersion was used.

[0153] Next, a coating solution and a coated substrate were produced in the same manner as in Example 1, except that this dispersion was used, and the properties were evaluated.

[0154] [Example 13] 4500g of titanium tetrachloride aqueous solution containing 2% by mass of titanium tetrachloride (calculated as TiO2) was mixed with 1760g of 15% by mass ammonia water to prepare a white slurry. The slurry was filtered and then washed with pure water to obtain 1800g of a cake with a solids concentration of 5% by mass. 2056g of 35% by mass hydrogen peroxide solution and 5144g of pure water were added to this, and the mixture was heated at 80°C for 1 hour to obtain 9000g of titanium peroxide aqueous solution containing 1% by mass of titanium peroxide (calculated as TiO2).

[0155] Next, 9000 g of this titanic acid peroxide aqueous solution was added to an aqueous dispersion prepared by diluting 92 g of an aqueous dispersion of silica alumina particles (JGC Catalysts and Chemicals, Ltd., Cataloid SN-350) with 5890 g of pure water. This aqueous dispersion was then heated in an autoclave at 165°C for 18 hours. The resulting aqueous dispersion was then cooled to room temperature and concentrated using an ultrafiltration membrane device. Subsequently, ion exchange was performed using a cation exchange resin to obtain 10472 g of an aqueous dispersion of titania silica particles with a solids concentration of 1% by mass.

[0156] To this aqueous dispersion, 79.9 g of tetraethoxysilane (manufactured by Tama Chemicals Co., Ltd.) containing 28.8 mass % of SiO2 as an organic silicon compound (R 100 mass parts of titania silica particles) was added. n -SiX 4-n After adding 22 parts by mass of toluene (as a metal oxide particle) and 10,472 g of methanol, the mixture was stirred for 19 hours at 50° C. After cooling the dispersion to room temperature, the dispersion medium was replaced with methanol by ultrafiltration, and the dispersion was concentrated to prepare a methanol dispersion of titania silica particles with a solid content concentration of 30% by mass as metal oxide particles.

[0157] To 425.8 g of this methanol dispersion of titania silica particles, 2.3 g of ammonia water with a concentration of 28% by mass and 10.5 g of pure water were added and stirred at room temperature for 0.5 hours. Next, 63.9 g of γ-methacryloxypropyltrimethoxysilane (R 100 parts by mass of titania silica particles) was added as an organic silicon compound. n -SiX 4-n The mixture was stirred at 50° C. for 19 hours to obtain a dispersion of surface-treated titania silica particles.

[0158] This dispersion of surface-treated titania silica particles was cooled to room temperature, and 2.1 kg of methanol (equivalent to five times the amount of the methanol dispersion of titania silica particles) was used to remove "unreacted and physically adsorbed organic silicon compounds" by ultrafiltration membrane method.

[0159] Next, the surface treatment with the above-mentioned γ-methacryloxypropyltrimethoxysilane was again carried out, and the "unreacted and physically adsorbed organosilicon compounds" were removed by the ultrafiltration membrane method, to produce a methanol dispersion of the surface-treated titania silica particles of the present invention having a solid content concentration as metal oxide particles of 30 mass%.

[0160] Next, a coating solution and a coated substrate were produced in the same manner as in Example 1, except that this dispersion was used, and the properties were evaluated.

[0161] [Example 14] A methanol dispersion of surface-treated silica particles was prepared in the same manner as in Example 2, except that γ-methacryloxyoctyltrimethoxysilane (KBM-5803 manufactured by Shin-Etsu Chemical Co., Ltd.) was used as the organosilicon compound.

[0162] Next, a coating solution and a coated substrate were produced in the same manner as in Example 1, except that this dispersion was used, and the properties were evaluated.

[0163] [Comparative Example 1] 6 g of γ-methacryloxypropyltrimethoxysilane (R per 100 parts by mass of silica particles) n -SiX 4-n A methanol dispersion of surface-treated silica particles was prepared in the same manner as in Example 1, except that 1 part by mass of the surface-treated silica particles was used.

[0164] Next, a coating solution and a coated substrate were produced in the same manner as in Example 1, except that this dispersion was used, and the properties were evaluated.

[0165] Comparative Example 2 A methanol dispersion of surface-treated silica particles was produced in the same manner as in Example 1, except that the second step was not carried out and a molecular sieve (3A 1 / 16 manufactured by Kanto Chemical Co., Inc.) was used to remove water and ammonia from the dispersion of surface-treated silica particles obtained in the first step, thereby adjusting the solid content concentration as metal oxide particles to 30 mass %.

[0166] Next, a coating solution and a coated substrate were produced in the same manner as in Example 1, except that this dispersion was used, and the properties were evaluated.

[0167] Comparative Example 3 A methanol dispersion of surface-treated silica particles was produced in the same manner as in Example 1, except that 2 kg of methanol (equivalent to the same amount as the methanol dispersion of silica particles) was used in the second step.

[0168] Next, a coating solution and a coated substrate were produced in the same manner as in Example 1, except that this dispersion was used, and the properties were evaluated.

[0169] Comparative Example 4 A methanol dispersion of surface-treated silica particles was produced in the same manner as in Example 2, except that 3750 g of an aqueous dispersion of silica particles (Spherica Slurry 160, manufactured by JGC Catalysts and Chemicals Co., Ltd., solid content concentration 16% by mass) was used.

[0170] Next, a coating solution and a coated substrate were produced in the same manner as in Example 1, except that this dispersion was used, and the properties were evaluated.

[0171] [Table 4]

[0172] [Table 5]

Claims

1. A dispersion of surface-treated metal oxide particles, comprising 3 to 60 parts by mass of an organosilicon compound having a functional group, as a solid content, per 100 parts by mass of metal oxide particles, the organosilicon compound in the liquid remaining after removing the surface-treated metal oxide particles from the dispersion is 0.20 parts by mass or less in terms of solid content relative to the metal oxide particles; the surface-treated metal oxide particles have an average primary particle size (D) of 5 to 120 nm as determined by image analysis, and the ratio (L / D) of the average particle size (L) of the surface-treated metal oxide particles as determined by dynamic light scattering to the average primary particle size (D) is 1.0 to 1.5; a ratio (A1 / A2) of a specific surface area (A1) of the surface-treated metal oxide particles determined by pulse NMR measurement of a methanol dispersion of the surface-treated metal oxide particles to a specific surface area (A2) of the metal oxide particles determined from an average primary particle diameter (F) of the metal oxide particles by image analysis is 0.30 to 0.

80.

2. 2. The dispersion according to claim 1, wherein the metal oxide particles contain at least one element selected from the group consisting of Si, Al, Sn, Sb, Ti, Zr, Zn, W, Fe, In, and Ba.

3. A first step of surface-treating the metal oxide particles by adding an organosilicon compound represented by the following formula (1) to a dispersion liquid containing the metal oxide particles; a second step of removing the organosilicon compound from the dispersion of surface-treated metal oxide particles obtained in the first step, the dispersion having a solid content concentration as metal oxide of 10 to 60 mass %, using a cleaning liquid amount per one time that is at least three times the amount of the dispersion, the surface-treated metal oxide particles in the dispersion obtained in the second step contain, as a solid content, 3 to 60 parts by mass of an organosilicon compound having a functional group per 100 parts by mass of the metal oxide particles; the organosilicon compound in the liquid remaining after removing the surface-treated metal oxide particles from the dispersion is 0.20 parts by mass or less in terms of solid content relative to the metal oxide particles; a ratio (L / D) of an average particle size (L) of the surface-treated metal oxide particles measured by a dynamic light scattering method to the average primary particle size (D) of the surface-treated metal oxide particles measured by an image analysis method is 1.0 to 1.

5. R n -SiX 4-n (1) (In the formula, R is an unsubstituted or substituted hydrocarbon group having 1 to 10 carbon atoms, X is an alkoxy group having 1 to 4 carbon atoms, a hydroxyl group, a halogen atom, or a hydrogen atom, and n is an integer of 0 to 4.)

4. 4. The method for producing a dispersion liquid of surface-treated metal oxide particles according to claim 3, wherein the first step and the second step are repeated in sequence after the second step.